PENDIDIKAN KESEHATAN PADA IBU HAMIL KEKURANGAN ENERGI KRONIS SEBAGAI UPAYA PENCEGAHAN STUNTING - Sutomo, Omo; Rumiatun, Darti; Rohaeti, Ayi Tansah; Ismiyati, Ismiyati; Nuraineu, Yaneu; Rokayah, Yayah (Jurnal Medikes (Media Informasi Kesehatan), 2024)
Toddlers with stunting in 2017 amounted to 22.2%. Many factors influence the incidence or risk of stunting in toddlers including the condition of the child and the mother. One of the factors from the mother includes the nutritional status of the mother and the mother's knowledge. This study used an experimental design approach (pre test - post test with control group design). The research sample was pregnant women with chronic energy deficiency with a total sample of 112 respondents (56 control group and 56 intervention group). This research was conducted at the Kalanganyar Health Center area, Lebak Regency in 2021. The results showed that the strength of the relationship between health education interventions and stunting prevention efforts was very strong and positive linear in nature (r=0.814) with a p value of=0.000. In addition, a p value of 0.000 was obtained, indicating that health education using pocket books had an effect on increasing maternal behavior in stunting prevention efforts.